Innovations in Human Resource Management: A Bibliometric Analysis - Redar Hameed Ali; Alena E. Fedorova (Changing Societies & Personalities)
The present study investigates how research related to innovation is constructed using various intellectual frameworks as well as identifies pertinent references, authors, themes, and journals. To do so, we employed bibliometric methodologies to analyze 1,947 papers published between 2003 and 2023. We identified three publication periods that influenced the development of research in this sector. In addition, we found that technological improvements in human resource management (HRM) have led to a transformation of worldwide operations thus providing numerous advantages to human resources departments. This study emphasizes the influence of technology on HRM, encompassing electronic databases, electronic HRM, and digital platforms. In addition, it shows that a theoretical basis has emerged for the classification of innovative technologies in HRM, which is essential to the development of new conceptual models of HRM in the digital era. In general, the study contributes to the body of literature on HRM and provides guidance for future research.